Virus-host protein-protein interactions as molecular drug targets for arboviral infections - Bhutkar, Mandar; Singh, Vishakha; Dhaka, Preeti; Tomar, Shailly (Frontiers in Virology, 2022)
Arboviruses have the potential to spread quickly and cause a global health emergency. These are RNA viruses that use RNA-dependent RNA polymerase (RdRp) for their replication. RdRp lacks proofreading activity, leading to high error rates, low replicative fidelity, and more genetic variability. In addition, shorter generation time and faster evolutionary rate of these viruses lead to re-emergence and recurrence of arboviral infections due to the emergence of new variants and the development of antiviral resistance. During the replication inside the host cell through protein-protein interactions (PPIs), these viruses interact with several host factors and utilize the host cellular machinery for their benefit; besides this, viruses employ several transmission strategies to combat host innate and adaptive immune responses by manipulating the signaling and metabolic pathways of the hosts. Hence, antiviral therapies targeting host-virus PPIs can provide an alternative broad-spectrum strategy against RNA viruses. The approach of targeting virus-specific proteins for developing antivirals is expected to solve the problem of antiviral drug resistance and combat emerging new variants of these viruses. This review focuses on host-virus PPIs of arboviral infections that directly affect the host immune signaling and metabolic pathways. Better understanding these mechanisms will develop new therapeutic tools to treat viral infections.